A Survey on Crwaling Strategy (International Journal of Advanced Research in Computer Science, 2017)
The vast collections of web pages are available on the Internet. Web search engine strives to gather information as more relevant as possible to the user is a hard task. Nowadays maintaining high efficiency is a difficult issue because of the large amount of information available on the web as well as deep web has dynamic nature. As crawler plays important role in such cases. Here we surveyed how the smart crawler can provide accuracy and highest harvest rate than other crawlers due to its two-stage framework. The first stage is site locating, the search engine can search highly ranking pages to avoid visit of a large number of pages. The second stage is a site exploring; it uses a link tree to balance link prioritizing of relevant links for fast searching.Keywords: Crawler, URLs, FFC, ACHE, Deep Web.